Enhancing the barangay information system by integrating geolocation technology and Tagalog chatbot using NLP algorithm for efficient community engagement and service - Cuevas, Joseph Allen A.; Gonzaga, Alexis Jermaine, Roque, Samuel Reign O. 4 0 16; 5 (2024)
u
Undergraduate Thesis: (Bachelor of Science in Information Technology) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2